2011
DOI: 10.1038/aps.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate enhances proliferation and differentiation of osteoblastic MC3T3-E1 cells via AMPK and eNOS activation

Abstract: Aim: To investigate the effects of bezafibrate on the proliferation and differentiation of osteoblastic MC3T3-E1 cells, and to determine the signaling pathway underlying the effects. Methods: MC3T3-E1 cells, a mouse osteoblastic cell line, were used. Cell viability and proliferation were examined using MTT assay and colorimetric BrdU incorporation assay, respectively. NO production was evaluated using the Griess reagent. The mRNA expression of ALP, collagen I, osteocalcin, BMP-2, and Runx-2 was measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…eNOS knockout mouse showed impaired osteogenic differentiation (Afzal et al 2004). Bezafibrate can promote the osteogenic differentiation of MC3T3E1 cells through regulating eNOS (Zhong et al 2011). In the present study, we found that treatment of human CV-MSCs with metformin led to an increase in the expression of eNOS.…”
Section: Discussionsupporting
confidence: 57%
“…eNOS knockout mouse showed impaired osteogenic differentiation (Afzal et al 2004). Bezafibrate can promote the osteogenic differentiation of MC3T3E1 cells through regulating eNOS (Zhong et al 2011). In the present study, we found that treatment of human CV-MSCs with metformin led to an increase in the expression of eNOS.…”
Section: Discussionsupporting
confidence: 57%
“…There is evidence for crosstalk between BMP and AMPK. BMP activation enhances AMPK signaling in vitro [16,46]. Moreover, AMPK activator agents increase both BMP and AMPK expression [14].…”
Section: Discussionmentioning
confidence: 99%
“…The pitavastatin treated osteoblasts showed increased expression level of BMP-2 mRNA in vitro; this effect was blocked when the cells were co-cultured with mevalonate or GGPP [75]. Additionally, simvastatin increased the mRNA expression for BMP-2 and stimulated MC3T3-E1 cells differentiation into osteoblastic cells, however, the cells pretreated with GGPP abolished simvastatin-induced differentiation [76].…”
Section: Accepted Manuscriptmentioning
confidence: 99%